2020
DOI: 10.1158/1078-0432.ccr-19-3538
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of AXL and HDAC Inhibition Reverses Mesenchymal Transition in Diffuse Intrinsic Pontine Glioma

Abstract: This study has been fully sponsored by the Semmy foundation (http://www.stichtingsemmy.nl), a non-profit organization that funds DIPG research.BGB324 was provided by BergenBio (Bergen, Norway). BergenBio was not involved in the design, execution or analysis of the experiments and did not participate in writing the manuscript.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…In the DKFZ-EP1NS model of EPN, SAHA induces neuronal differentiation associated with loss of stemness (Milde et al, 2011). As noted above, HDACi effects in H3K27M DIPG cells involve a decrease in stemness gene expression (Meel et al, 2020). These findings support the view that HDACis should be further investigated as prodifferentiating and stemness modulating agents in pediatric brain tumors.…”
Section: The Role Of Modulating Stemness and Differentiationsupporting
confidence: 65%
See 1 more Smart Citation
“…In the DKFZ-EP1NS model of EPN, SAHA induces neuronal differentiation associated with loss of stemness (Milde et al, 2011). As noted above, HDACi effects in H3K27M DIPG cells involve a decrease in stemness gene expression (Meel et al, 2020). These findings support the view that HDACis should be further investigated as prodifferentiating and stemness modulating agents in pediatric brain tumors.…”
Section: The Role Of Modulating Stemness and Differentiationsupporting
confidence: 65%
“…Combined treatment with the HDACi panobinostat and the AXL inhibitor BGB324 resulted in synergistic antitumor effects on DIPG cells, with reduced expression of genes related to mesenchymal phenotype, stemness, and DNA damage repair (Meel et al, 2020). HDACis also synergize with blockade of bromodomain inhibition or CDK7, which disrupts oncogenic transcription, in DIPG models.…”
Section: Diffuse Intrinsic Pontine Gliomamentioning
confidence: 98%
“…Consistent with previous reports that evaluated broad-spectrum HDAC inhibitors 17,22,31,32 , panobinostat showed strong efficacy in vitro. However, CUDC-907, a dual-acting inhibitor of class I PI3K and HDAC 33 , had higher median AUC and was slightly more selective for pHGG models.…”
Section: High-throughput Screen For Drug Response Of Different Phgg Ssupporting
confidence: 91%
“…A more expansive in vitro followed by in vivo screen of the combinatorial druggable DMG landscape, with clinically relevant factors such as potency and blood–brain-barrier penetrance taken into account, revealed the proteasome inhibitor marizomib combined with panobinostat as the most promising pairing [ 88 ]. Additional in vivo studies have suggested inhibition of lysine demethylase [ 89 , 90 ], DNA methylation [ 63 ], AXL kinase [ 91 ], and PI3K [ 92 ] as promising combination strategies with panobinostat, several of which are now in clinical trials.…”
Section: Development Of Novel Therapiesmentioning
confidence: 99%